Young American Muslims : Dynamics of Identity - Kabir, Nahid Afrose (Book collections on Project MUSE., 2013)
An examination of the identity of young Muslims in America This book presents a journey into the ideas, outlooks and identity of young Muslims in America today. Based on around 400 in-depth interviews with young Muslims from Florida, Maryland, Massachusetts, Michigan, New York and Virginia, all the richness and nuance of these minority voices can be heard. Many young Americans cherish an American dream, 'that all men are created equal'. And the election of America's first black President in 2008 has shown that America has moved forward. Yet since 9/11 Muslim Americans have faced renewed challenges, with their loyalty and sense of belonging being questioned. Investigates the identity of ethnic and racial groups such as Iranians, Arab Americans and African Americans Discusses the impact of the American media on young Muslims Introduces debates on the Israeli-Palestine issue Analyses President Obama as a national and world leader